Along the archival grain epistemic anxieties and colonial common sense - Stoler, Ann Laura 1949- (Princeton University Press, 2009)
Along the Archival Grain offers a unique methodological and analytic opening to the affective registers of imperial governance and the political content of archival forms. In a series of nuanced mediations on the nature of colonial documents from the nineteenth-century Netherlands Indies, Ann Laura Stoler identifies the social epistemologies that guided perception and practice, revealing the problematic racial ontologies of that confused epistemic space. Navigating familiar and extraordinary paths through the lettered lives of those who ruled, she seizes on moments when common sense failed and prevailing categories no longer seemed to work. She asks not what colonial agents knew, but what happened when what they thought they knew they found they did not. Rejecting the notion that archival labor be approached as an extractive enterprise, Stoler sets her sights on archival production as a consequential act of governance, as a field of force with violent effect, and not least as a vivid space to do ethnography